2019
DOI: 10.47176/mjiri.33.24
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting health expenditures in Iran using the ARIMA model (2016-2020)

Abstract: Background policymakers t calculated total Methods: Au study, five-yea Results: App predict these co to 2698346 bil 2020. Conclusion: need for contin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The promotion of health is a moral obligation, including the social and economic categories. Thus, every health treatment service planning should be part of the pervasive attitude of healthcare policy to make part of the integrated plan of sustainable development [ 2 ]. Most of the world’s countries have faced rising health treatment section expenses during the recent decade [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The promotion of health is a moral obligation, including the social and economic categories. Thus, every health treatment service planning should be part of the pervasive attitude of healthcare policy to make part of the integrated plan of sustainable development [ 2 ]. Most of the world’s countries have faced rising health treatment section expenses during the recent decade [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that report, the source and method of forecasts for 2019 remain unknown, and some may assess the results as optimistic and some others pessimistic. Furthermore, Ramezanian et al [ 47 ] have used the autoregressive integrated moving average (ARIMA) forecasting model to project the health figure of 2020 in Iran. The results showed that the total health spending by government and households will increase 75% during the years 2016–2020.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most commonly used prediction techniques in the evaluation and monitoring epidemiological surveillance [ 20 26 ]. The ARIMA model consists of auto regressive (AR) model, moving average (MA) model, seasonal auto regressive integrated moving average (SARIMA) model and etc [ 17 , 27 ]. If the data of research showed evidence of seasonal tendency, the seasonal auto regressive integrated moving average (SARIMA) model should be used [ 28 ].…”
Section: Methodsmentioning
confidence: 99%